Rancang Bangun Aplikasi Prototype Sistem Penjualan Kopi Berbasis Mobile (Study Kasus: Kedai Cuan) - Luri Sesy Apriyani; Diah Aryani; Ahmad Fathurrozi (Journal of Informatic and Information Security, 2024)
One of the shops in Tangerang that is attractive to young people because of its relatively cheap price is Kedai Cuan, this shop offers various types of coffee with a comfortable atmosphere. The absence of an application that can increase Kedai Cuan's online sales has led to a decline in sales, as shown by the current sales report. In addition, customers still have difficulty finding information about the available menu, and customers still have to place orders and make payments manually. This research aims to build an Android-based online sales system needed to speed up the sales process at Kedai Cuan with a system development method using the prototype method and the React Native framework JavaScript programming language and Supabase database so that it is hoped that this application can make it easier for owners and customers to buy and sell online and increase sales.